Stakeholders’ perceptions and attitudes towards ecotourism development in Alamout, Iran - Asadi, Azita (2014)
The traditional lifestyles, conservative mindsets, a reluctance to see change in their natural environment and low education of rural communities are barriers to the development of ecotourism. As such, the consequential dearth of facilities that result in potential ecotourism destinations is a deterrent to tourists. The Alamout area of Iran possesses natural and historical attractions but remains undeveloped for these reasons. The ecotourism industry is very closely related to the visitors, local communities and resource managers and it is imperative that they, as stakeholders, must show support for as well as interest and involvement in ecotourism and its development for the industry to be successful. In many literatures, it has been shown that most researchers have focused on the locals while some have considered visitors but too little attention has been paid to the area of ecotourism development support and involvement through investigations of the points of view of different stakeholders. Three core theories were combined to achieve synergy between stakeholders’ perception of impacts, their intention to be involved in and give support to Ecotourism development in the area. Both the Theory of Reasoned Action and Theory of Planned Behaviour were used to derive the concept of intention and behaviour through respondents’ attitude and perceptions. Social Exchange Theory explicates each person’s involvement in different activities concerning the advantages and tangible or intangible profits. Stakeholders Theory posits that an industry’s success depends on its ability to manage relationships with its stakeholders and explains that people try to care for and conserve everything which has value for them. First, positive and negative impacts derived from literature were discussed and finalised with administrators relevant to this study area. Then data were collected from visitors to four major tourism sites in the Alamout area and from members of the local communities living in the six villages around these sites during the period from June to September 2011. Structural equation modelling was used to find the relation between items and their high level latent variables using AMOS. Of the study population, 451 persons completed the questionnaire including 236 visitors and 215 locals. In both groups, males were dominant due to cultural attitudes. Local communities mostly consisted of white beard leaders and high council members of the villages and their jobs were highly dependent on natural resources, such as agriculture and gardening. Visitors were mostly young students or small families working in government organizations. Outcomes of the study indicate that a positive relation exists between total positive impact perceptions and intentions to be involved in Ecotourism development among the visitors and locals. Results of both models indicate a negative statistically significant relation between total negative impact perceptions of visitors and locals and their intentions to be involved in Ecotourism development. Visitors and locals expressed high support for Ecotourism development. They expressed support for establishing infrastructure and indicated their agreement with establishing a domestic museum and organising traditional festivals. They believed that Ecotourism has a vital role to play in the future and agreed that the Tourism organization should plan for Ecotourism development in the Alamout area.